Bibliometric and Content Analysis: The Role of Sustainable Manufacturing in Fertilizer Distribution - Ahmad Ryan Andriansyah; Imam Baihaqi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The fertilizer industry has a strategic role in supporting food security, however challenges in inefficient distribution can hamper the sustainability of the agricultural sector. This research aims to analyze publication trends related to sustainable manufacturing in fertilizer distribution and its impact on Environmental, Social and Governance (ESG) aspects. Data was obtained from the Scopus and Web of Science databases with a total of 723 articles from Scopus and 763 articles from Web of Science. After filtering based on document type (articles and reviews), language (English), access (open access), and year of publication (2015-2024), 167 articles remained for analysis. The research methods used are bibliometric analysis to identify publication patterns, co-word analysis, and content analysis to explore main findings in the literature. The research results show that the application of sustainable manufacturing in fertilizer distribution has a positive impact on environmental, social and governance aspects. The use of technology such as Distribution Planning and Control System (DPCS) and Truck Tracking (INDIGO Tracker) increases distribution efficiency by reducing carbon emissions and fuel consumption. Web-based distribution information systems improve transparency and accountability, minimize waste and ensure timely distribution. On the social side, programs such as the Farmers Card help equalize access to fertilizer for farmers, reducing social inequality. In the governance aspect, this technology strengthens supervision and increases trust between farmers and stakeholders. The results of this research also confirm that a sustainability-based approach in fertilizer manufacturing and distribution can be an effective strategy to support more efficient and environmentally friendly agriculture.